THE RELATIONSHIP OF ORAL HEALTH AND QUALITY OF LIFE FOR ELDERLY AT THE TRESNA WERDHA NIRWANA SOCIAL ORGANIZATION PURI SAMARINDA - Alifia Auralia; Nuryanni Dihin Utami; Endang Sawitri; Ellina Martalina; Ronny Isnuwardana; Cicih Bhakti Purnamasari (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Elderly is the final stage of the aging process, usually followed by cumulative changes in human that create changes in the oral cavity as well. Oral Health plays a crucial role in general health and quality of life. Material and Methods: : This research used analytical observational study with cross-sectional design, using purposive sampling as its sampling method. The respondents were 81 elderly people. This research used oral health Levin questionnaire and Oral Health Impact Profile (OHIP-14). The data from this research were analyzed using Spearman correlation test. Results and Discussions: The correlation between dental and oral health and quality of life showed significant with the p value <0.001 and correlation coefficient R= 0.657. Conclusion: There was a significant correlation between dental and oral health and the quality of life of elderly people in Tresna Werdha Nirwana Puri Samarinda Nursing home.